Pengaruh strategi bauran pemasaran terhadap harga pada home industri jenang “Mirah” Ponorogo - Prasetiyani Ika Saputri (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
Of this study was to determine the marketing mix strategy in Home Industry Jenang "MIRAH" in Ponorogo, to determine the pricing of products in Home Industry Jenang "MIRAH" in Ponorogo. Marketing Mix Strategy is one factor in the price. The samples in this study using sampling techniques saturated as many as 39 people. Sampling using techniques sampling. Results of simple linear regression Y = 43,477 + 0,558 X, meaning that if the price increase of 1%, then marketing mix strategy will increase by 0,558 if other factors held constant. It is obtained from tcount on marketing mix strategy variable (X) is 9,440 with 0,000signifkansi level. Because 9,440 >1,68488 and 0.000 < 0.05, which expressed their rejection of Ho means the marketing mix strategy effect on price. It can be concluded that thitung > ttable ie, greater than t table of a significance level of 0.000 t less than 0.05 then the research hypothesis reject Ho and accept Ha. While the results of R2 of 0.670, indicating that 67% strategy marketing mix variables influenced the price, while the remaining 33% is influenced by other factors not examined. Conclusion there is the effect of strategy marketing mix on price satisfaction in Home Industry Jenang "MIRAH" in Ponorogo.